Laser Power Transmission and Its Application in Laser-Powered Electrical Motor Drive: A Review - Liu Hongzuo (Sciendo, 2021)
Laser power transmission (LPT) is considered a potentially efficient way for power delivery, especially in long-distance wireless applications and harsh hazardous environmental conditions. In contrast to other wireless power transmission (WPT) methods, LPT has many advantages such as lower device size, focused transmitting direction and high power density. With the development of technology, LPT has been widely adopted in several fields. In conservative industries, the utilisation of LPT can resolve the limitation problem in a wired connection. The adverse influence of electromagnetic interference (EMI) concerning application and high-temperature fields can be reduced. This paper will give a simple review of LPT and demonstrate the basic concept of a photoelectric emitter, transmission channel and receiver material. Based on the recent research about diode laser beam combining technology and high-efficiency multi-junction photovoltaics (PV) materials, the advised LPT devices for simple application as laser power motor will be simply discussed.